Fabrication of high-quality or highly porous graphene sheets from exfoliated graphene oxide via reactions in alkaline solutions. (November 2018) - Cho, Joon Young; Jang, Jeong In; Lee, Won Ki; Jeong, Soo Yeon; Hwang, Jun Yeon; Lee, Heon Sang; Park, Jong Hwan; Jeong, Seung Yol; Jeong, Hee Jin; Lee, Geon-Woong; Han, Joong Tark
Abstract: The applications of solution-exfoliated graphene oxide (GO) as an electrical/electrochemical conductor require rational design–based approaches. Herein, we show that reduced GO nanosheets with highly ordered or nanoporous structures can be fabricated by treatment of graphite oxide (GrO) having variable-oxidation-degree with hot KOH solution. As model systems, GrO powders fabricated by modified Brodie and Hummers methods (B-GrO and H-GrO, respectively) were exfoliated into GO in alkaline solutions (to afford B-KGO and H-KGO, respectively), followed by 2.5-h refluxing at 100 °C. Notably, B-KGO was exceptionally resistant to hot KOH solution, whereas H-KGO was partially reduced under these conditions, as confirmed by 13 C solid-state NMR, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy analyses. Moreover, reduced B-KGO featured highly ordered structures, whereas reduced H-KGO contained nanopores resulting from low-temperature activation in KOH solution. These extraordinary reactions of KGO nanosheets were translated into different electrical properties of reduced KGO nanosheets and different rheological properties of the corresponding pastes. Graphical abstract: High-quality or highly porous graphene nanosheets were rationally fabricated by oxidation degree–dependent transformations of graphene oxide in hot alkaline solution. These reactions were translated into exceptionally different electrical properties of reduced graphene oxide nanosheets and the different rheological properties of the corresponding pastes. Image 1